Pengaruh Current Ratio Dan Working Capital Turnover Terhadap Net Profit Margin Pada PT Indofood Sukses Makmur Tbk Periode 2010-2022 - Amelinda Clara Alverina; Nina Shabrina (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The purpose of this study was to determine the effect of Current ratio and Working Capital Turnover on Net Profit Margin at PT Indofood Sukses Makmur Tbk for period 2010-2022. The method used is a quantitative method. The sampling technique used is purposive sampling in the form of the financial statements of PT Indofood Sukses Makmur Tbk for 13 years for the period 2010-2022 The method used in this study is a quantitative research method. This data was analyzed using multiple linear regression analysis which was processed through IBM Eviews software version 13. The results of this study are the Current Ratio has significant effect on Net Profit Margin with and hypothesis testing is obtained t count > t table or (2,927371 > 1,8125). Working Capital Turnover has significant effect on Net Profit Margin with hypothesis testing obtained t count > t table or (3,136072 > 1,8125). Hypothesis test obtained value of F arithmetic > F table or (11,73981 > 4,10), Current Ratio and Working Capital Turnover have significant effect on Net Profit Margin with the regression equation Y = -0.008184 + 0.105778(CR) + 0.066761(WCT) + ɛ. The value of the coefficient of determination is 78,16% while the remaining 21,84% is influenced by other factors.